2006
DOI: 10.1016/j.sbi.2006.08.005
|View full text |Cite
|
Sign up to set email alerts
|

N-linked glycan recognition and processing: the molecular basis of endoplasmic reticulum quality control

Abstract: Nascent polypeptides emerging into the lumen of the endoplasmic reticulum (ER) are Nglycosylated on asparagines in Asn-Xxx-Ser/Thr motifs. Processing of the core oligosaccharide eventually determines the fate of the associated polypeptide by regulating entry into and retention by the calnexin chaperone system, or extraction from the ER folding environment for disposal. Recent advances have shown that at least two N-glycans are necessary for protein access to the calnexin chaperone system and that polypeptide c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
84
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 49 publications
3
84
0
Order By: Relevance
“…In particular, protein glycans are recognition signals for the entry to and exit from the ER protein folding apparatus involving calnexin (CNX) and calreticulin (CRT). Many reviews have been written on the subject, including Helenius and Aebi (2004), Moremen and Molinari (2006), Caramelo and Parodi (2008), and a recent article about CRT in plants (Jia et al, 2009). Two N-acetylglucosamine (N1 and N2, gray squares) and five mannose residues (M3 to M7, gray, pink, and blue circles) are added subsequently to the polyisoprenoid lipid dolichol (Dol) on the cytoplasmic side of the ER.…”
Section: Protein N-glycosylationmentioning
confidence: 99%
“…In particular, protein glycans are recognition signals for the entry to and exit from the ER protein folding apparatus involving calnexin (CNX) and calreticulin (CRT). Many reviews have been written on the subject, including Helenius and Aebi (2004), Moremen and Molinari (2006), Caramelo and Parodi (2008), and a recent article about CRT in plants (Jia et al, 2009). Two N-acetylglucosamine (N1 and N2, gray squares) and five mannose residues (M3 to M7, gray, pink, and blue circles) are added subsequently to the polyisoprenoid lipid dolichol (Dol) on the cytoplasmic side of the ER.…”
Section: Protein N-glycosylationmentioning
confidence: 99%
“…Calnexin has been implicated in several genetic diseases caused by inherited protein folding defects (Amaral, 2004;Chevet et al, 1999;Kuznetsov and Nigam, 1998;Ni and Lee, 2007). Mechanistically, calnexin interacts with nascent polypeptides as a lectin that binds N-linked glycan, and/or via protein-protein contacts (Bedard et al, 2005;Caramelo and Parodi, 2008;Helenius and Aebi, 2004;Marechal et al, 2004;Moremen and Molinari, 2006;Thammavongsa et al, 2005;Williams, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility has been suggested that they are partially rescued by BiP, suggesting the presence of a fail-safe mechanism in the system in ER. 37) II. Functional Analysis of Glycoprotein Glycans by Using Chemically Synthesized Probes…”
Section: Biosynthesis and Processing Of N-glycosylated Proteins Anmentioning
confidence: 99%